2019
DOI: 10.15171/jlms.2019.13
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Photobiomodulation Therapy on Post-Surgical Pain

Abstract: Introduction: One of the major complains after surgery is pain. Recent advances in the prevention and reduction of postoperative pain have provided several modalities. One of them is the use of laser irradiation on the surgical area. Objectives: To evaluate the effects of low level laser therapy (LLLT) on pain and side effects after surgery. Methods: In this research, databases such as: PubMed, Science Direct, Google Scholar, Springer and Cochrane were used and the words of laser therapy, photobiomodulation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 38 publications
1
18
0
11
Order By: Relevance
“…The full text of 34 remaining articles was screened and 15 articles were excluded [1][2][3]6,7,9,10,[23][24][25][26][27][28][29][30] because: the PEDro score of three studies was 6 2,3,28 . Six articles didn't report pain by VAS; it was not possible to estimate ES in two studies 1,6,7,9,10,23,24,27 ; two studies 29,30 were case reports; and two studies did not have at least one another group for comparison. 25,26 Finally, 19 studies (HILT: 11, +other interventions: 8) were included for qualitative and quantitative assessment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The full text of 34 remaining articles was screened and 15 articles were excluded [1][2][3]6,7,9,10,[23][24][25][26][27][28][29][30] because: the PEDro score of three studies was 6 2,3,28 . Six articles didn't report pain by VAS; it was not possible to estimate ES in two studies 1,6,7,9,10,23,24,27 ; two studies 29,30 were case reports; and two studies did not have at least one another group for comparison. 25,26 Finally, 19 studies (HILT: 11, +other interventions: 8) were included for qualitative and quantitative assessment.…”
Section: Resultsmentioning
confidence: 99%
“…1,4,5 Low-power laser (light) therapy (power ≤ 500 mW) can be used to decrease acute and chronic pain, induce recovery of damaged nerves, enhance peripheral circulation and metabolism, and reduce joint inflammation. 2,5,6 The effects of low-power laser therapy are photochemical not thermal. In a recent review, Cotler et al concluded that low-power laser therapy is a new cost-effective therapy for musculoskeletal pain, which improves the quality of life and reduces financial strains.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conservative treatment is usually the initial choice, in which physiotherapeutic modalities are included, among them, joint mobilization and manipulation [8,9], fascial manipulation [10], electrotherapy [11], therapeutic ultrasound [12] and photobiomodulation (PBM) [13]. PBM with the low-level laser therapy (LLLT) associated with a light emitting diode (LED) (Cluster) [8] with therapeutic purposes, such as increased RNA, DNA and ATP synthesis, fibroblast cell proliferation rate and collagen synthesis, increased vascularization and variations in nerve conduction [15][16][17]. In isolation, LLLT has been shown to be effective, both in clinical and experimental studies in several conditions helping to control pain, reduce the inflammatory process and speed-up tissue repair [18][19][20][21], but not without controversial outcomes [22].…”
Section: Introductionmentioning
confidence: 99%